NILAI PENGAJARAN DALAM EPIK I LA GALIGO (KAJIAN HERMENEUTIKA) - Fitriansal Fitriansal (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
The value of teaching in the epic I La Galigo is expected to be a reference for other research and a consideration in carrying out educational development in Indonesia. Providing awareness about the existence of learning values contained in local wisdom as a legacy that is owned in Indonesia so that it can provide a perspective on the development of education in Indonesia. This study uses a reflective/reflective method with Schleiermacher's hermeneutic study on text analysis and text reconstruction. The data used as the object of study is the epic manuscript I La Galigo episode We Cudai Gives Birth to I La Galigo. Data analysis is in accordance with using qualitative data analysis. The results of the study show that the epic I La Galigo episode We Cudai Gives Birth to I La Galigo has pedagogic value, especially in teaching value. The concept of character formation, teacher knowledge and inspiration is embodied in the discovery of meaning in the text above. There are teaching values about responsibility, sacrifice, orientation, scientific mastery and the ability to provide reinforcement by a teacher to instill mindset, principles, knowledge, intelligence, criticality and analysis. ability of students.